2006
DOI: 10.1634/stemcells.2004-0351
|View full text |Cite
|
Sign up to set email alerts
|

Very Low O2 Concentration (0.1%) Favors G0 Return of Dividing CD34+ Cells

Abstract: STEM CELLS 2006;24: 65-73

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
90
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(99 citation statements)
references
References 52 publications
(73 reference statements)
8
90
0
1
Order By: Relevance
“…3A, 3B) to CRA CFC (data not shown). Thus, hypoxia-resistant STR-type LSC seem to be a more homogeneous, mostly cycling cell subset, whereas STR-HSC are less homogeneous and relatively more quiescent [2,5,13]. This conclusion that stem cell hierarchy within the MEL cell population is different from normal is in keeping with current views on the issue [20].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…3A, 3B) to CRA CFC (data not shown). Thus, hypoxia-resistant STR-type LSC seem to be a more homogeneous, mostly cycling cell subset, whereas STR-HSC are less homogeneous and relatively more quiescent [2,5,13]. This conclusion that stem cell hierarchy within the MEL cell population is different from normal is in keeping with current views on the issue [20].…”
Section: Discussionsupporting
confidence: 67%
“…This study was based on the adaptation to leukemia cells [11,12] of the CRA assay developed in our laboratory [2] and successfully applied [3,5,7,13] for the quantification in vitro of the stem cell potential of normal hematopoietic cell populations. The CRA assay, in combination with incubation under severe hypoxia as a selection procedure, showed that the MEL cell population includes highly hypoxia-sensitive CFC as well as their hypoxia-resistant, CRC-type progenitors.…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies have been performed with cord blood cells (Hermitte et al, 2006). The authors reported preferential survival of primitive HSC among cord blood CD34 + cells in cultures under 0.1% O 2.…”
Section: Oxygen Reactive Oxygen Species and Antioxidantssupporting
confidence: 72%
“…Several studies have suggested that long term HSCs reside mainly in the endosteal sites of the BM, in which the pO 2 is very low (3,6). Cell biological studies using HS(P)Cs indicated that their functions as well as their quiescence state are maintained most effectively under hypoxic conditions (10,(47)(48)(49)(50)(51)(52). Hypoxia stabilizes the HIF-1␣ protein, a master regulator of oxygen homeostasis, and activates HIF-1␣-mediated signals in HSCs (48,53,54).…”
Section: Discussionmentioning
confidence: 99%